Building a Research Data Management Service at the University of California, Berkeley: A tale of collaboration. (March 2017) - Wittenberg, Jamie; Elings, Mary
University of California, Berkeley's Library and the central Research Information Technologies unit have collaborated to develop a research data management program that leverages each organization's expertise and resources to create a unified service. The service offers a range of workshops, consultation, and an online resource. Because of this collaboration, service areas that are often fully embedded in IT, like backup and secure storage, as well as services in the Library domain, like resource discovery and instruction, are integrated into a single research data management program. This case study discusses the establishment of the program, the obstacles in implementing it, and outcomes of the collaborative model.